PENERAPAN JARIMATIKA BERBASIS DIGITAL UNTUK MENINGKATKAN COUNTING SKILLS PADA PEMBELAJARAN MATEMATIKA MATERI PERKALIAN SISWA KELAS III SDN 171/I BAJUBANG LAUT - Alfina Febrianti; Destrinelli; Akhmad Faisal Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of implementing a digital-based jarimatika method to improve counting skills in mathematics learning, specifically on multiplication material, for third-grade students at SDN 171/I Bajubang Laut.This research employs Classroom Action Research (CAR), which focuses on how the implementation of digital-based jarimatika can improve the counting skills of third-grade students at SDN 171/I Bajubang Laut. Data were collected through observation and tests. The research subjects consisted of 15 third-grade students, comprising 7 male and 8 female students.The results of the study indicate that the implementation of digital-based jarimatika through the use of visual and systematic digital media is able to assist students in performing multiplication calculations. The teacher explained how to use the digital-based jarimatika method by providing calculation examples and guiding students to practice directly, thereby encouraging active student participation in the learning process. This research was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection, with two meetings in each cycle. The findings show that the implementation of digital-based jarimatika successfully increased students’ counting skills, with the percentage rising from 53.3% in Cycle I to 81.6% in Cycle II.